Beyond the plate: How socio-culture and economics drive sustainable diets globally - Baliwati, Yayuk Farida; Rusyda, Akifa Laila (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Sustainable diets play a powerful catalyst in unlocking and scaling health and climate solutions. Many studies on the diets focus only on health and environmental concerns, but barely consider related socio-cultural and economic determinants.Objective: The present systematic review provides an overview of socio-cultural and economic determinants on sustainable diets across income countries.Methods: Electronic databases, including MDPI, PubMed, Science Direct, and The Lancet Planetary, were performed. The systematic review was conducted following the PRISMA principles. Human studies among all population groups in income countries were included, and require at least one socio-cultural and economic determinant on sustainable diet. The search focused on studies that were peer-reviewed and published in English between 2010 and 2024. The Newcastle-Ottawa scale and its modified version were used to assess the methodological quality (risk of bias).Results: Forty-two of the 2,443 articles identified attained the inclusion criteria. Almost all included studies were cross-sectional (n=39; 92.8%) and 3 cohort studies. The publications covered 56 country-based study settings, five of which were conducted as multi-site studies. Most studies focused on high-income countries, mostly in Europe, Central Asia, and North America. All included studies found 15 socio-cultural and economic determinants; 10 studies of socio-cultural determinants and 5 studies of economic determinants on sustainable diets. The systematic review found that socio-cultural and economic determinants on sustainable diets were divided into external drivers (ethnicity, gender, cultural belief, spiritual belief, geographical settings, political ideology, and food price) and personal drivers (educational level, nutritional knowledge, marital status, household size, income level, occupation, food expenditure, and household food security status).Conclusion: Addressing the social, cultural, and economic determinants is prerequisite for transforming more-sustainable diets. Food sustainability and food and nutrition security are aligned at the individual and household level. Comprehensive strategies targeting multiple levels, and multiple settings are required to enhance dietary changes on sustainable diets.Keywords: Determinant; economic; food choice; socio-culture; sustainable diets